Efficacy Analysis and Prognostic Impact of Sivelestat Sodium in Coronavirus Disease 2019-Related Acute Respiratory Distress Syndrome - Xiao Che; Wei Hu; Ziying Zhang; Lexiao Wang; Zhe Xu; Fusheng Wang (Pharmaceuticals, 2024)
Purpose: This study aimed to evaluate the efficacy of sivelestat sodium on mortality, oxygenation index, and serum markers in patients with acute respiratory distress syndrome (ARDS) associated with Coronavirus Disease 2019 (COVID-19). Methods: A retrospective analysis was conducted on adult inpatients admitted to the Intensive Care Unit (ICU). The study compared clinical characteristics, laboratory indices, and mortality rates between patients treated with and without sivelestat sodium. Cox regression analysis was employed to assess the effect of sivelestat sodium on the risk of death, oxygenation index, and improvement of serum markers in patients with COVID-19-associated ARDS. Results: A total of 110 patients with COVID-19-associated ARDS were included, with 45 patients in the sivelestat group and 65 patients in the control group. The overall patient mortality rate was 69.1%, with 62.2% in the sivelestat group and 73.8% in the control group. After five days of treatment, the median change from baseline in the oxygenation index was 21 mmHg in the medicated group and −31 mmHg in the control group (p < 0.05). Analysis of the oxygenation index as a clinical endpoint event showed a significantly higher rate of improvement in the sivelestat group compared to the control group (57.8% vs. 38.5%, p < 0.05), and the odds of raising the oxygenation index after treatment were 2.05 times higher in the sivelestat group than in the control group (HR = 2.05, 95%CI: 1.02–4.15, p < 0.05). Among patients with a baseline oxygenation index < 200 mmHg, patients in the sivelestat group had an 86% lower risk of death compared to the control group (HR = 0.14, 95%CI: 0.02–0.81, p < 0.05). Conclusions: Sivelestat sodium demonstrated a significant improvement in the oxygenation index of patients with COVID-19-associated ARDS and was found to considerably reduce the risk of death in patients with a baseline oxygenation index of <200 mmHg.